Structural changes and relaxations monitored by luminescence. (18th April 2012) - Wang, Y; Yang, B; Townsend, PD
Abstract: Luminescence data have often been used to study imperfections and to characterize lattice distortions because the signals are sensitive to changes of structure and composition. Previous studies have included intentionally added probe ions such as rare earth ions to sense distortions in local crystal fields caused by modified structural environments. An under‐exploited extension of this approach was to use luminescence to monitor crystalline phase changes. A current overview of this new and powerful technique shows that continuous scanning of the sample temperatures immediately offered at least three types of signatures for phase transitions. Because of high sensitivity, luminescence signals were equally responsive to structural changes from inclusions and nanoparticles. These coupled to the host material via long‐range interactions and modified the host signals. Two frequently observed examples that are normally overlooked are from nanoparticle inclusions of water and CO2. Examples also indicated that phase transitions were detected in more diverse materials such as superconductors and fullerenes. Finally, luminescence studies have shown that in some crystalline examples, high dose ion implantation of surface layers could induce relaxations and/or structural changes of the entire underlying bulk material. This was an unexpected result and therefore such a possibility has not previously been explored. However, the implications for ion implication are significant and could be far more general than the examples mentioned here. Copyright © 2012 John Wiley & Sons, Ltd.